DUAL STAINING IDENTIFIES A GREATER PROPORTION OF MORIBUND SPERMATOZOA IN STALLION SEMEN WITH POOR CRYOTOLERANCE - PAUL, NILENDU; TALLURI, T R; YASHPAL,; LEGHA, R A; NAG, PRADEEP; KUMARESAN, ARUMUGAM (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to evaluate the functional membrane integrity of cryopreserved spermatozoafrom stallions belonging to two contrasting motility groups (high and low motility groups). A dual staining methodcomprising of carboxy fluoroscein diacetate (CFDA) and propidium iodide (PI) was used for this purpose. Stallionswere classified into either high (post thaw progressive motility e”35%) or low (post thaw progressive motility
Keywords: Stallion; spermatozoa; motility; membrane integrity; dual staining